2002
DOI: 10.1046/j.1365-2141.2002.03888.x
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of point‐of‐care prothrombin time testing in a community clinic: a randomized crossover comparison with hospital laboratory testing

Abstract: Summary. The success in achieving therapeutic international normalized ratio (INR) targets in the control of warfarin using a whole-blood point-of-care testing (POCT) monitor (CoaguChek) in a community clinic was compared with hospital laboratory coagulometer prothrombin time (PT) testing in a randomized crossover study. Forty-six patients were randomized into two groups. At each visit, capillary blood was taken for the POCT monitor and venous blood for the laboratory coagulometer. In Group 1, for 6 months, do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
54
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 20 publications
6
54
0
Order By: Relevance
“…In a recent report, the accuracy of this device, when compared to laboratory methods, showed a mean INR bias of negative 0.025, with the least amount of bias at INRs between 2.0 and 3.0 [52]. Another study demonstrated that there was no significant difference between the geometric mean INRs obtained from the CoaguChek system and laboratory systems [53]. Tripodi et al [47] evaluated the ISI calibration of this device based on an IRP and found it to be extremely close to that adopted by the manufacturer for both whole blood and plasma.…”
Section: Coaguchek Systemmentioning
confidence: 94%
“…In a recent report, the accuracy of this device, when compared to laboratory methods, showed a mean INR bias of negative 0.025, with the least amount of bias at INRs between 2.0 and 3.0 [52]. Another study demonstrated that there was no significant difference between the geometric mean INRs obtained from the CoaguChek system and laboratory systems [53]. Tripodi et al [47] evaluated the ISI calibration of this device based on an IRP and found it to be extremely close to that adopted by the manufacturer for both whole blood and plasma.…”
Section: Coaguchek Systemmentioning
confidence: 94%
“…There have been few RCTs in this area and none have investigated all the areas covered in this Trial or at the scale of this Trial either in terms of the number of practices, the number of patients or the number of pathology tests included. 8,18,33,34,[58][59][60] No past trials and very few observational studies 16,17 have investigated the influence of geographic location on PoCT. The results of the PoCT Trial should provide a sound evidence base as to whether PoCT (for the three conditions) should be implemented by the government in Australian general practice.…”
Section: Resultsmentioning
confidence: 99%
“…44 Four of the RCTs investigated PoCT with another intervention. 8,18,21,34,58,59 The geographical setting included the United Kingdom (n=13) 8,16,18,21,33,[60][61][62][63][64][65][66][67] , Australia (n=7) 17,23,47,[68][69][70][71] , USA (n=5) 44,58,[72][73][74] , Belgium (n=2) 34,59 , Sweden (n=1) 75 and Ireland (n=1). 76 A description of the 29 studies included in the review is reported in Table 13 and Table 14.…”
Section: Excluded Studiesmentioning
confidence: 99%
“…Various studies have proven the good correlation between the Coaguchek S™ system and laboratory measurements 3,13,14 . Medical centers like the Mayo Clinic have used the technology of these devices to manage their patients 6 .…”
Section: Discussionmentioning
confidence: 98%
“…This test is very easy to perform and can be conducted anywhere including the patient's home, primary care facilities or hospitals 3,4 . These devices use microfluid technology and various detection methods to generate a prothrombin time measurement eliminating the need to draw peripheral venous blood.…”
mentioning
confidence: 99%